(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Capital is considered to be a very important factor in the production process. Any type of business requires capital so capital is that part of wealth that is used in the production process to increase output. A common concept of capital is that part of man-made wealth that is used in the production process to increase output.